PERAMALAN PERSEDIAAN BAHAN BAKU DAUN KAYU PUTIH DI AGROINDUSTRI MINYAK KAYU PUTIH KUPANG KOTA MOJOKERTO - Syahri, Ria Misdin; Hidayat, Syarif Imam; Winarno, Sri Tjondro (Berkala Ilmiah AGRIDEVINA, 2020)
Forecasting is an attempt to see the situation and conditions in the future by estimating the influence of the situation and conditions in the future on developments in the future. Forecasting the supply of raw materials at Kupang Eucalyptus Oil Agroindustry is not maximal because there are still residual raw materials of Eucalyptus leaves that are not processed within 1x24 hours. Therefore, efforts are needed so that the planning of raw eucalyptus leaves is appropriate so that it can meet the management principles of effective, efficient and rational in decision making. This research  aims to predict the remaining amount of raw material in the following year. This research was carried out at Kupang Eucalyptus Oil Agroindustry in Mojokerto City using secondary data. Data collection methods used are interviews with relevant parties and retrieve historical data at the study site. The analysis used in this study is the Monte Carlo Simulation. The results showed that in 2020 the remaining raw material is predicted to increase by 3.18% from 2019. DOI : https://doi.org/10.33005/adv.v9i1.2141